2021
DOI: 10.1136/bmjopen-2020-044416
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in activities of daily living and readmission in older patients with heart failure: a cohort study

Abstract: ObjectivesThis study aims to investigate the prevalence of impairment of activities of daily living (ADLs) in older patients with heart failure (HF), and to examine the impact of ADL impairment on readmission after discharge.Design and settingsA prospective cohort study was conducted in patients aged ≥65 years with HF admitted to a tertiary hospital in Vietnam from August 2016 to June 2017. Difficulties with six ADLs were assessed by a questionnaire. Participants were classified into two categories (with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…29,32,37,50) (Supplementary Table2). One study reported findings based on a cross-sectional and a cohort study (36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29,32,37,50) (Supplementary Table2). One study reported findings based on a cross-sectional and a cohort study (36).…”
mentioning
confidence: 99%
“…Functional disability was defined as the need for assistance or inability to perform ADL or IADL. Of the 27 studies reporting on ADL, 15 studies used Barthel Index(14, 17, 20-22, 24, 28, 29, 32, 34-36, 43, 48, 50), while several studies reported the use of Katz scale(22,28,29,33,39,42,44) and other ADL assessments. The Lawton and Brody scale was used in 14 studies to assess IADL(14, 17, 26, 27, 30-32, 34, 39, 41-44, 49).…”
mentioning
confidence: 99%
“…In this review, 5 studies were occurred in America (10,(13)(14)(15)(16), 4 in Asia (7,8,12,17) and 3 in Europe (11,18,19). The prevalence of ADL impairment in HF patients ranged from 11.1 to 70.5%.…”
Section: Basic Information Of the Included Studiesmentioning
confidence: 99%
“…ADL ability in HF patients is closely related to their prognosis. A study showed that patients with ADL impairment had an approximately threefold increase in 3-month readmission rates compared to patients without ADL impairment ( 7 ). Another study showed that ADL ability was an independent predictor of all-cause mortality in patients with HF ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…19 Zvláště u starších hospitalizovaných pacientů se srdečním selháním je běžná porucha v oblasti aktivit každodenního života, což je spojeno se zvýšeným počtem rehospitalizací. 20 Ztráta soběstačnosti a negativní změny v oblasti aktivit denního života mohou být u starších pacientů hospitalizovaných pro akutní dekompenzaci srdečního selhání spojeny i s vyšší nemocniční mortalitou. 21 Parametry, jako je soběstačnost pacienta, je proto nutné zhodnotit při přijetí pacienta do péče, aby mohli být identifi kováni rizikoví pacienti s cílem plánovat vhodnou rehabilitační intervenci, která by měla zabránit dalšímu propadu v této oblasti, což by mohlo pomoci zlepšit klinický management tohoto stavu.…”
Section: Diskuseunclassified